The Fascinating Elephants - Naidu, M. Kamal (International Journal of Bio-resource and Stress Management, 2010)
The article presents some interesting facts about the behavior and life of the elephants as experienced by the author. It is all about the glory and misery of wild elephants as members of their herd. Over thirty years of his work in several zoos and sanctuaries in India and Kenya the author shares his observations and experiences on the elephants including mahwat (elephant rider) ranging from elephants’ affection, intuition, fear, desire and struggle to lord the herd, to miserable death at the end of life.